2016
DOI: 10.1002/adma.201604744
|View full text |Cite
|
Sign up to set email alerts
|

High Open‐Circuit Voltages in Tin‐Rich Low‐Bandgap Perovskite‐Based Planar Heterojunction Photovoltaics

Abstract: ] Of relevance to this work is the binary metal perovskite CH 3 NH 3 (Pb x Sn 1-x )I 3 [0 ≤ x ≤ 1]. [30,31] Interestingly, the bandgap bows and becomes lower when Sn 2+ is substituted by Pb 2+ for samples with 80% and 60% Sn content compared to 100% Sn-based perovskite, in line with previous observations. [30,31] While such tin-based perovskites offer tunable bandgaps down to 1.1 eV, the fabrication of efficient optoelectronic devices has been impeded by factors including poor semiconductor quality and low sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
248
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(267 citation statements)
references
References 69 publications
(110 reference statements)
12
248
4
1
Order By: Relevance
“…This means that trap-assisted recombination is present in both solar cells and is the dominating loss mechanism 24, 25 . The light-intensity-dependent V OC can provide critical insights into the recombination mechanism in the solar cells 26 . For V OC measurement, the device is open circuit, so there is no current extraction from the devices, and all photo-generated carriers recombine in Sb 2 Se 3 film.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that trap-assisted recombination is present in both solar cells and is the dominating loss mechanism 24, 25 . The light-intensity-dependent V OC can provide critical insights into the recombination mechanism in the solar cells 26 . For V OC measurement, the device is open circuit, so there is no current extraction from the devices, and all photo-generated carriers recombine in Sb 2 Se 3 film.…”
Section: Resultsmentioning
confidence: 99%
“…For V OC measurement, the device is open circuit, so there is no current extraction from the devices, and all photo-generated carriers recombine in Sb 2 Se 3 film. Thus, the carrier recombination process can be reflected based on the relationship of V OC ∝ n ( k B T/q )ln( I ), where k B is the Boltzmann constant, T is the temperature and q is elementary charge 2629 . n ( k B T/q ) is the slope of V OC vs. the natural logarithm of light-intensity ln( I ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous reports, the partial Sn substitution in lead halide PVSK resulted in broadened absorption from 800 nm to 900 nm. Most recently, Sadhanala et al [116] reported a novel elevated temperature processing method to fabricate MASn x Pb 1−x I 3 (0 ≤ x ≤ 1) thin films, obtaining large micron-sized grains with almost complete surface coverage (Figure 12c,d). In their film fabrication process, the temperature of the hotplate was elevated to 240 °C after the deposition of PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate)) layer.…”
Section: B-site Mixed Pvskmentioning
confidence: 99%
“…Since the excitation photon energy is higher than the bandgap, this PL signal is caused by one-photon excitation. [14,33] Therefore, the sharp band-edge absorption profile reflects the low defect density of the single crystal. By using a 1028 nm excitation pulse with a pulse fluence of 36 µJ cm −2 , the PL spectrum under two-photon excitation was clearly observed at 579 nm as shown by the black solid line in Figure 1a.…”
mentioning
confidence: 99%